Mitochondrial RNA granules are critically dependent on mtDNA replication factors Twinkle and mtSSB - Hensen, Fenna (Nucleic Acids Res, 2019)
Newly synthesized mitochondrial RNA is concentrated in structures juxtaposed to nucleoids, called RNA granules, that have been implicated in mitochondrial RNA processing and ribosome biogenesis. Here we show that two classical mtDNA replication factors, the mtDNA helicase Twinkle and single-stranded DNA-binding protein mtSSB, contribute to RNA metabolism in mitochondria and to RNA granule biology. Twinkle colocalizes with both mitochondrial RNA granules and nucleoids, and it can serve as bait to greatly enrich established RNA granule proteins, such as G-rich sequence factor 1, GRSF1. Likewise, mtSSB also is not restricted to the nucleoids, and repression of either mtSSB or Twinkle alters mtRNA metabolism. Short-term Twinkle depletion greatly diminishes RNA granules but does not inhibit RNA synthesis or processing. Either mtSSB or GRSF1 depletion results in RNA processing defects, accumulation of mtRNA breakdown products as well as increased levels of dsRNA and RNA:DNA hybrids. In particular, the processing and degradation defects become more pronounced with both proteins depleted. These findings suggest that Twinkle is essential for RNA organization in granules, and that mtSSB is involved in the recently proposed GRSF1-mtRNA degradosome pathway, a route suggested to be particularly aimed at degradation of G-quadruplex prone long non-coding mtRNAs.